Coral Settelment on Concrete Artifical Reefs in Pramuka Island Eaers, Kepulauan Seribu, Jakarta and Management Option - Aziz, Arif Miftahul; Kamal, Mohammad Mukhlis; Zamani, Neviaty Putri; Subhan, Beginer (Journal of Indonesian Coral Reefs, 2011)
Latest stage development of recruit coral community in concerete artificial reefs were observed for nine months (from October 2009 to July 2010) by visual cencus and underwater photography methods. Amounts of 10 units of concrete artifical reef deployed in Pramuka Island waters and Gosong Pramuka in 2011 were used as an objects in this reseacrh. As a comparation, the conditios of coral coverand reef fishes in natural reef were observed by line intercept transcet, visual census, and underwater photography methods. In order to measure coral coberage area  we used a ImageJ 1.42q software. In march 2010, amounts of 457 coral colonies from 21 genera and 216 coral colonies from 16 genera were found on artifical reefs surface in Station 1 (Pramuka Island) and Station 2 (Gosong Pramuka) respectively. Number pf recruit coral colonies was dominated by genus Porites. Pocillopora, and Chypastrea. In july 2010, the precentage of coral cover on cencrete artifical refs reaches 41.46 ±13.37% (±SD) in Station 1 and 20. ±6.08% (mean ±SD) in Station 2, while the percentage of coral coverage on natural reefs were 23.14% and 40.43% in Station 1 and 2 respectively. Genus Porites become the most dominant genus in both of stations in terms recruit coloby abudance and percent cover. This result shows that concrete artificial reefs can effectively use to create new habitat of corals, coral fishes and other biota particularly in degraded coral reefs ecosystem.